2014
DOI: 10.1136/annrheumdis-2014-206334
|View full text |Cite
|
Sign up to set email alerts
|

The incidence and prevalence of systemic lupus erythematosus in the UK, 1999–2012

Abstract: ObjectivesTo estimate the incidence and prevalence of systemic lupus erythematosus (SLE) in the UK over the period 1999–2012.MethodsA retrospective cohort study using the Clinical Practice Research Datalink (CPRD). The incidence was calculated per 100 000 person-years and the prevalence was calculated per 100 000 people for the period 1999–2012 and stratified by year, age group, gender, region and ethnicity. Three definitions of SLE were explored: (1) systemic lupus, (2) a fully comprehensive definition of lup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
202
3
14

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 262 publications
(225 citation statements)
references
References 25 publications
(28 reference statements)
6
202
3
14
Order By: Relevance
“…Lupus is a chronic multiorgan disease with a prevalence that ranges from 20 to 51 per 100,000 in Canada (28,29) and 78 to 97 per 100,000 in other countries (30,31) that has been shown to have a negative impact on work and work participation (32,33). It is estimated that 60% of people with lupus experience some form of activity limitations at work (34).…”
Section: Introductionmentioning
confidence: 99%
“…Lupus is a chronic multiorgan disease with a prevalence that ranges from 20 to 51 per 100,000 in Canada (28,29) and 78 to 97 per 100,000 in other countries (30,31) that has been shown to have a negative impact on work and work participation (32,33). It is estimated that 60% of people with lupus experience some form of activity limitations at work (34).…”
Section: Introductionmentioning
confidence: 99%
“…(5) In January 2013 there were 660 practices contributing records for approximately 12 million people. The CPRD has been previously described and validated (6,7), but in brief practices enter data on patient demographics, diagnoses, consultations and prescriptions using Vision Practice Management Software. Diagnoses are recorded using Read codes, a standard clinical terminology system used in general practice in the UK.…”
Section: Source Populationmentioning
confidence: 99%
“…A recent UK retrospective cohort study also confirmed the highest incidence and prevalence of SLE in people with black Caribbean ethnicity and a higher prevalence in Asian compared to white patients [9]. Similarly, in a large French nationwide study, the prevalence of SLE was also much higher in the Caribbean overseas areas and lowest in the French northwestern metropolitan territories [10].…”
Section: Ethnicity and Prevalence Of Systemic Lupus Erythematosusmentioning
confidence: 69%
“…The increasing prevalence of SLE in the UK [9], despite an annual decline in its incidence by 1.8%, may supposedly result from a better outcome of patients with SLE, but this remains to be confirmed also for nonwhite ethnicities. The outcome of black patients with LN is significantly worse both in terms of patient survival (the 5-, 10- and 15-year patient survival was 76, 65 and 55% in blacks compared to 87, 76 and 70% in whites [13]) and renal survival (the 5-year survival without doubling of serum creatinine was 63% in blacks and 88% in whites [39]).…”
Section: Ethnicity and Outcome Of Sle And Lnmentioning
confidence: 99%